Factors influencing medication label viewing in Malaysia - Cheah, Yong Kang; Chong, Yen Wan (SAGE Publications Ltd, 2018)
The misuse of medicine is a serious public health issue worldwide. An important factor that contributes to the misuse of medicine is the lack of medication label viewing by consumers.The objective of the present study is to examine the socio-economic, demographic and lifestyle factors associated with medication label viewing among Malaysian adults.The empirical analysis is based on a nationally representative data set of 30,992 respondents. An ordered probit model is used to examine different types of medication label viewers.The results of this study suggest that socio-economic (i.e. age, income level, education level, location of residence), demographic (i.e. gender, ethnicity, marital status) and lifestyle factors (i.e. physical activity, smoking) have significant effects on medication label viewing. It is found that age, low-income and low-education level reduce the likelihood of viewing medication label.Based on these findings, several policy implications are suggested. The present study provides policy makers with baseline information regarding which cohorts of individuals to focus on in efforts to increase the frequency of medication label viewing.